Effect of whey protein supplementation on weight and body composition indicators: A meta-analysis of randomized clinical trials. (August 2022) - Sepandi, Mojtaba; Samadi, Mohammad; Shirvani, Hossein; Alimohamadi, Yousef; Taghdir, Maryam; Goudarzi, Forough; Akbarzadeh, Isa
Abstract: Background & aim: Whey protein (WP) is one of the well-known dairy driven products to help people to change their weight and body composition (BC). This study aimed to investigate the effect of WP on weight and BC on every published RCT on all populations. Methods: A systematic review of the literature was undertaken to identify RCTs that examined the effect of WP on weight, body fat, lean body mass, fat-free mass, and waist circumference. To create weighted-group-mean differences for within- and between-group comparisons, random effects models were used. Subgroup analyses were also done to determine the effect of potential sources of heterogeneity. Results: Thirty-five RCTs, with a total of 1902 adult participants were included in pooled analysis. The effect of WP supplementation on BMI (−0.156, 95% CI: −0.31, 0.00, P < 0.05), body fat mass (−0.144, 95% CI: −0.28, 0.00, P < 0.05), and waist circumference (−0.448, 95% CI: −0.86,  −0.03, P < 0.05) in within group analysis, and BMI (−0.769, 95% CI: −1.54, 0.00, P < 0.05) and lean body mass (0.741, 95% CI: 0.07, 1.41, P < 0.05) in the between group analysis was indicated. Resistance training, WP dosage, sex, age group, the type of control group (placebo, different proteins, etc.), the control group dosage, and energy intake before and during the trial, as well as between the WP and control groups, were recognized as the main sources of heterogeneity. Conclusion: The data from trials currently available supports the use of WP to improve BC indicators. The benefits of WP on BC are expected to be greatest when combined with resistance training and a reduction in overall calorie consumption.